Effects of Foods of Mesoamerican Origin in Adipose Tissue and Liver-Related Metabolism - Alejandra Meza-Rios; Erika Fabiola López-Villalobos; Luis Alberto Anguiano-Sevilla; Sandra Luz Ruiz-Quezada; Gilberto Velazquez-Juarez; Rocío Ivette López-Roa; Ana Laura Marin-Molina; Adelaida Sara Minia Zepeda-Morales (Medicina, 2023)
Adipose tissue and liver metabolism play a key role in maintaining body homeostasis; therefore, their impairment conduces a pathological state. Nowadays, occidental lifestyle is a common etiological issue among a variety of chronic diseases, while diet is a unique strategy to prevent obesity and liver metabolism impairment and is a powerful player in the treatment of metabolic-related diseases. Mesoamerican foods are rich in bioactive molecules that enhance and improve adipose tissue and liver performance and represent a prophylactic and therapeutic alternative for disorders related to the loss of homeostasis in the metabolism of these two important tissues.